Expression Analysis of Stemness Genes in a Rat Thyroid Cell Line FRTL5 - Shimasue, A.; Yamakawa, N.; Watanabe, M.; Hidaka, Y.; Iwatani, Y.; Takano, T. (Experimental and Clinical Endocrinology & Diabetes, 2015)
Detection and analysis of a small subpopulation of cells such as stem cells or cancer stem cells are recognized to be a key technique in a recent regeneration and cancer science. However, in the thyroid, no marker that identifies stem cells has been established yet. We previously established a novel method to analyze cells collected by fluorescence-activated cell sorting (FACS), named mRNA quantification after FACS (FACS-mQ). By using this method, the biological characteristics of the sorted cells can be determined by analyzing their gene expression profile. In this study, we analyzed the expression of stemness genes in a rat thyroid cell lines FRTL5 using FACS-mQ. 3 stemness genes, NANOG, ABCG2 and GATA4, were expressed in FRTL5. In FRTL5 cells, varied expression of thyroglobulin (TG) among cells was observed by flow cytometry. Cell populations with high or low TG expression were analyzed by FACS-mQ. The cell population with low TG expression showed increased expression of the stemness genes. Furthermore, Ki67-positive cells showed increased expression of TG, which suggested that cells with high TG proliferated rapidly. These results indicated that FRTL5 contains a cell population with high stemness gene expression and less differentiated features, resembling stem cells. These cells might regulate proliferation in FRTL5.
Keywords: FACS-mQ; thyroglobulin; TTF1; flow cytometry; quantitative RT-PCR